The Pengaruh Penggunaan Media Pembelajaran Wordwall terhadap Hasil Belajar Peserta Didik di SMAN 51 Jakarta - Ade Jordy Setiawan; Munandar, Aris; Jalaluddin, Muzani (Geography Education Study Program, Universitas Kanjuruhan Malang, 2024)
This study aims to determine the effect of learning media Wordwall based website on the learning outcomes of the cognitive domain of students in the material on the spread of culture in class XI SMA Negeri 51 Jakarta. This research is included in the type of experimental research with a quantitative approach and research design, namely Pre-Test and Post-Test Control Group Desain which uses 2 types of classes, namely the experimental class and also the control class. In this study using analysis techniques by conducting instrument tests with validity and reliability tests, data testing by processing the results data Pre-Test and Post-Test, and test data analysis with normality test, homogeneity test and test Independent Simple T-Test. And this research can be concluded with the acquisition of test results Independent Simple T-Test with the number 0.000 which means that H0 rejected and Ha accepted which has a reference to the value of Sig. < 0.05. It can be concluded that there is a positive effect on increasing cognitive learning outcomes in class XI SMAN 51 Jakarta after using media-based learning website or application Wordwall in learning Geography on the sub-material of the Distribution of Indonesian Cultural Diversity.